Evaluation of nitrate in shallow groundwater at Pasirkoja of Bandung City, Indonesia, using the pollution index and the nitrate pollution index methods - Naily, Wilda; Sunardi, Sunardi; Asdak, Chay; Hendarmawan, Hendarmawan (Journal of Degraded and Mining Lands Management, 2024)
Pasirkoja is an old residential area in Bandung City currently densely populated. Some people in Pasirkoja use shallow groundwater for washing and bathing, and some for cooking. Pollutants very easily pollute shallow groundwater, and nitrate is one of the pollutants found in shallow groundwater in residential areas. The water quality status was determined using the pollution index (PI) method based on a Decree of the Minister of Environment Number 115 of 2003 and the nitrate pollution index (NPI) to ascertain the shallow groundwater quality in Pasirkoja of Bandung City, Indonesia. The variables used in the PI method were pH, turbidity, total dissolved solids (TDS), nitrate, and nitrite, while the NPI method used the nitrate parameter. Shallow groundwater samples were taken during the rainy season and dry season. Based on the PI method, the results showed that the quality status of shallow groundwater at the research location is mostly lightly polluted in the rainy and dry seasons. Meanwhile, based on the NPI method, most are clean (not polluted). Differences in the quality status of shallow groundwater depend on the environmental conditions around which shallow groundwater samples were taken. The research results also showed that, based on the PI method, nitrate is not the main parameter that determines pollution at the research location.